HGF/Met Signaling Is a Key Player in Malignant Mesothelioma Carcinogenesis - Gaudino, Giovanni (Biomedicines, 2014)
Malignant mesothelioma (MM) is a highly aggressive cancer related to asbestos or erionite exposure and resistant to current therapies. Hepatocyte Growth Factor (HGF) and its tyrosine kinase receptor Met regulate cell growth, survival, motility/migration, and invasion. HGF and Met are expressed in MM cells, suggesting that the HGF/Met signaling plays a role in development and progression of this tumor, by autocrine and/or paracrine mechanisms. Upregulation and ligand-independent activation of Met, which is under suppressive control of miR-34 family members, correlate with enhanced invasion, migration and metastatic potential in several cancers, including MM. Moreover, Simian Virus 40 (SV40) Tag expression also induces a HGF autocrine circuit in an Rb-dependent manner in human mesothelial cells (HM) and possibly other cell types, enhancing cell adhesion, invasion and angiogenesis. The resulting activation of Met causes HM transformation and cell cycle progression, and contributes to virus particle assembling and infection of adjacent cells. The constitutive activation of Met, frequently occurring in MM, has been successfully targeted in preclinical models of MM. In conclusion, Met expression, activation state, subcellular localization and also HGF co-receptors expression, such as CD44, have clinical relevance for novel targeted therapies in a cancer for which no effective treatment is currently available.